2021
DOI: 10.1002/cphc.202100516
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Thermal Transport in the Homogeneous Cage‐Like Compounds Cu3VSe4 and Cu3NbSe4: Interplay between Phonon‐Phase Space, Anharmonicity, and Atomic Mass

Abstract: Understanding the correlation between crystal structure and thermal conductivity in semiconductors is very important for designing heat-transport-related devices, such as high-performance thermoelectric materials and heat dissipation in micronano-scale devices. In this work, the lattice thermal conductivity (k L ) of the cage-like compounds Cu 3 VSe 4 and Cu 3 NbSe 4 was investigated by experimental measurements and first-principles calculations. The experimental k L of Cu 3 NbSe 4 is approximately 25 % lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Alternatively, sulvanite-type Cu 3 MX 4 (M = V, Nb, and Ta; X = S, Se, and Te) compounds have been regarded as promising photoabsorbers for the conversion of solar energy into electricity and fuels due to their extraordinary properties, including tunable bandgap energy, high optical absorption coefficient, and readily available and comparatively abundant elements. [22][23][24][25][26][27][28][29] For example, Ikeda et al reported that Cu 3 Nb 1−x V x S 4 shows promise for application in photocatalytic H 2 evolution under visible light irradiation. 30 Liu et al reported that Cu 3 VS 4 nanocrystals can be tuned from plasmonic-like to excitonic simply via coating with CdS shells.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, sulvanite-type Cu 3 MX 4 (M = V, Nb, and Ta; X = S, Se, and Te) compounds have been regarded as promising photoabsorbers for the conversion of solar energy into electricity and fuels due to their extraordinary properties, including tunable bandgap energy, high optical absorption coefficient, and readily available and comparatively abundant elements. [22][23][24][25][26][27][28][29] For example, Ikeda et al reported that Cu 3 Nb 1−x V x S 4 shows promise for application in photocatalytic H 2 evolution under visible light irradiation. 30 Liu et al reported that Cu 3 VS 4 nanocrystals can be tuned from plasmonic-like to excitonic simply via coating with CdS shells.…”
Section: Introductionmentioning
confidence: 99%